Investigation of the topography of magnetron-deposited Cu/Ni multilayers by X-ray reflectometry and atomic force microscopy - Kucharska, Barbara; Kulej, Edyta; Kanak, Jarosław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
This paper presents the results of research of Cu/Ni multilayers magnetron-deposited on an Si (100) substrate. The thickness of Cu sublayers was identical in all multilayers and equalled 2 nm. The thickness of Ni sublayers varied between 1.2 and 3.0 nm. The surface topography of the multilayers was examined using the AFM (research of different areas). The interface roughness and period thickness were characterized by X-ray reflectometry (XRR). The roughness of the multilayers achieved by the XRR method was very similar for all 0.6 nm samples examined. However, the values of the roughness parameter Ra obtained by AFM examination were in the range of 0.09–0.32 nm, and depended on the size of the area examined. Based on the function obtained from the AFM measurements, taken on surface areas varying in size, an area of 1.5–4.0 cm2 was determined, for which an agreement between the roughness parameter, as determined by the AFM method, and the XRR method results would be expected.
Optica Applicata, Vol. 39, 2009, nr 4, s. 881-888
Keywords: optyka; multilayers Cu/Ni; X-ray reflectometry (XRR); atomic force microscopy (AFM); roughness